Understanding the context of male and transgender sex work using peer ethnography. (23rd March 2009) - Collumbien, M; Qureshi, A A; Mayhew, S H; Rizvi, N; Rabbani, A; Rolfe, B; Verma, R K; Rehman, H; Naveed-i-Rahat,
Abstract : Objectives: To distinguish between three distinct groups of male and transgender sex workers in Pakistan and to demonstrate how members of these stigmatised groups need to be engaged in the research process to go beyond stated norms of behaviour. Methods: A peer ethnography study was undertaken in a major city in Pakistan. 15 male and 15 transgender sex workers were trained as peer researchers to each interview three peers in their network. Analysis was based on interviews with peer researchers as well as observation of dynamics during training and analysis workshops. Results: The research process revealed that, within the epidemiological category of biological males who sell sex, there are three sociologically different sexual identities: khusras (transgender), khotkis (feminised males) and banthas (mainstream male identity). Both khusras and khotkis are organised in strong social structures based on a shared identity. While these networks provide emotional and material support, they also come with rigid group norms based on expected "feminine" behaviours. In everyday reality, sex workers showed fluidity in both behaviour and identity according to the situational context, transgressing both wider societal and group norms. The informal observational component in peer ethnography was crucial for the accurate interpretation of interview data. Participant accounts of behaviour and relationships are shaped by the research contexts including who interviews them, at what stage of familiarity and who may overhear the conversation. Conclusions: To avoid imposing a "false clarity" on categorisation of identity and assumed behaviour, it is necessary to go beyond verbal accounts to document the fluidity of everyday reality.